Mineralogical and geochemical characterization of a rare ultramafic lamprophyre in the Tandilia belt basement, Río de la Plata Craton, Argentina - Dristas, Jorge A. (2013)
A metre-thick ultramafic lamprophyre dyke intrudes the basement of the andilia belt at the Sierra Alta de Vela, Argentina. A petrological and geochemical study of this rock and associated small dykes indicates a predominantly calc-alkaline trend. Phlogopite KeAr dating of the ultramafic lamprophyre gave a minimum age of 1928 +/- 54 Ma as a late event of the Transamazonian Orogeny, which is well represented in the basement of the Tandilia belt. An electron microprobe study indicates the presence of phlogopite,albite, chromite and Cr-rich phenocrysts and Cr-free microphenocrysts of diopside as primary minerals. Subsequent to deformation at the contacts with the wall rock, metasomatism generated strongly zoned amphibole (edenite, pargasite, Mg-hastingite and tremolite compositions) and andradite as well as chlorite, sericite, albite,apatite and calcite. The central zone of the lamprophyre is almost undeformed and exhibits some ocellar texture. Geochemical and isotopic signatures of the lamprophyre suggest that its magma source may have previously undergone incompatible element enrichment of the mantle source, representing the original precursor magma for the calc-alkaline dyke series of the Sierra Alta de Vela.